Comparative analysis of electroencephalographic tests of alpha activity attenuation in evaluation of involuntary falling asleep in healthy adults - Šundrić Zvonko; Rajšić Nenad; Lakočević Milan; Nikolić-Đorić Emilija (Srpski Arhiv za Celokupno Lekarstvo, 2010)
Introduction. Decrease of daily alertness is a common cause of accidents in the work place, especially traffic accidents. Therefore, an increasing interest exists to determine reliable indicators of a tendency to fall asleep involuntarily. Objective. To determine an optimal electroencephalographic (EEG) indicator of an involuntary tendency to fall asleep, we performed a study on neurologically healthy subjects, after one night of sleep deprivation. Total sleep deprivation was aimed at increasing daily sleepiness in healthy subjects, providing us with an opportunity to test different methods of evaluation. Methods. We applied a visual analogue scale for sleepiness (VASS), EEG registration with the specific test of alpha activity attenuation (TAA) in 87 healthy subjects. The test was performed in a standard way (sTAA) as well as in accordance with new modifications related to changes of EEG filter width in the range from 5 to 32 Hz (mTAA). Results. After sleep deprivation, we observed involuntary falling asleep in 54 subjects. The comparison of VASS results showed no differences, contrary to a more objective TAA. Between two variants of TAA, the modified test provided us with a better prediction for subjects who would fall asleep involuntarily. Conclusion. The application of a more objective EEG test in evaluation of daily alertness represents the optimal method of testing. Modified TAA attracts special attention, offering a simple solution for reliable testing of decreased daily alertness in medical services related to professional aircraft personnel.